TERRORISM AND RADICALISM, THREATS FOR IDEOLOGY PANCASILA - Chandra, Alex (Awang Long Law Review, 2018)
The values of Pancasila have been believed to be true by the Indonesian people. Therefore, practicing Pancasila is a must for the Indonesian nation. Positive attitudes in practicing Pancasila values include respect for family members, respect for the elderly, accepting life sparingly, discriminating friends, accepting deliberations for consensus, performing worship in accordance with their respective religions, and helping others in distress according to their own ability. And, the understanding of religious harmony is an understanding of the concept of living together without any disputes that cause divisions or disputes among religious people. With a clear understanding, then if we apply harmonious life in the interaction of religious people, then we will not encounter or experience a negative attitude or condition with religious reasons. As for those who consider NKRI not pelu that is 0.38 percent and not important 1.51 percent. Only 20 percent consider it necessary and 78.11 rate is still important. From the survey conducted, 37 percent of East Kalimantan residents consider teachers and lecturers who are institutionalized education is the most responsible for the four pillars of the state become part of life. Besides teachers and lecturers, community leaders are considered responsible by approximately 28.3 percent of respondents, 4.9 percent political figures. While 23 percent of the community considers the need to establish a special body.